Passage of Change Law, Society and Governance in the Pacific - Jowitt, Anita (ANU Press, 2010)
Numerous issues face Pacific states trying to find their way in the early 21st century. Countries are striving to secure the benefits of modernisation. Governance, law and order are needed to reach such a goal, but development cannot be at the price of culture or the environment. The question of how to develop and maintain sound legal systems and legal rules whilst maintaining the unique cultural heritages within the Pacific is a challenge with no easy answer. This interdisciplinary collection locates issues of law and governance within the particular socio-political context of the Pacific island region, presenting sociological, anthropological and political insights alongside jurisprudential analysis. Key issues including corruption, the role of customary law in modern legal systems, the place of human rights in the Pacific, environmental issues and the structure of the state are explored from a variety of perspectives.